Dream: Digital Media Transformation as an Optimization of Deep Learning Implementation - Cahyo Apri Setiaji; Ike Yunia Pasa; Astri Srigustini; Tengku Maaidah bin Tengku A Razak (Universitas Muhammadiyah Mataram, 2026)
The background of the research is the low effectiveness of the implementation of elementary school students' deep thinking skills that have not facilitated the development of deep thinking skills. The aim of the research is to increase the effectiveness of deep learning implementation for students. The type of research and development (R&D) adopts the Borg and Gall approach. The subjects of the study were 33 elementary school students. Data collection used observation, validators, tests and questionnaires. Data analysis used descriptive, t-test, and N-Gain. The results of the data analysis showed that the Dream media was able to improve deep thinking skills through the t-test Sig. (2-tailed) 0.000 <0.05, meaning there was a significant difference between the pretest and posttest scores. The results of the N-Gain effectiveness test showed a score of 0.81> 0.7, including the high category. The hypothesis test showed a significant increase in the average score from 66 to 82 so it was concluded that Dream was able to develop deep thinking skills. The implication of this research is that learning media based on Articulate Storyline is a solution to increase learning participation, cooperation, and develop deep thinking skills.